New insights into the role of serum amyloid A (SAA) on obesity and insulin resistance - Oliveira, Edson Mendes de (2015)
Chronic low-grade endotoxemia is an important player in obesity and insulin resistance associated to a high-fat diet (HFD). On the other hand, although it is known that intense endotoxemia and infection reduce appetite and induce intense catabolism, leading to weight loss during the acute inflammatory phase, the late effects of an intense endotoxemia were previously unexplored. Here we report that, besides the concurrent effects, multiple and intense endotoxemia causes long lasting biochemical alterations in the adipose tissue that intensify the harmful effects of a HFD. Mice submitted to multiple and severe endotoxemia had increased the adipose tissue expression of TLR-4, CD14 and SAA3, remaining altered after one week in recovery. When associated to a HFD, mice previously submitted to acute endotoxemia showed a more severe weight gain and impaired insulin sensitivity. Adopting the HFD as an obesogenic stimulus, we evaluated the participation of the protein serum amyloid A (SAA) in obesity development. Using a SAA-targeted antisense oligonucleotide, we observed that the depletion of SAA prevented metabolic alterations, endotoxin elevation, weight gain and insulin resistance in a diet-induced obesity protocol. Inadequate sleep is another important factor to be considered in the obesity epidemic. We found that sleep restriction (SR) causes biochemical and morphological alterations in mice adipose tissue. The levels of serum resistin and the adipose tissue mRNA expression of resistin, TNF-α and IL-6 were increased after SR. When associated to a HFD, mice previously submitted to SR gained more weight with increased macrophage infiltration in the epididymal adipose tissue, and insulin resistance. SAA is also part of the initial biochemical alterations caused by SR. It was observed that the expression of SAA in liver and adipose tissue is upregulated, with return to baseline when sleep is restored. Furthermore, 48 hours of total sleep restriction in healthy human volunteers also caused a serum elevation in SAA concentrations. Considering that SAA induces cell proliferation, we suggest that situations with an increase in SAA production and the consecutive preadipocyte proliferation would prime the adipose tissue to further adipocyte differentiation and hypertrophy. Furthermore, we suggest that SAA alter LPS signaling, possibly inhibiting its clearance. The mechanism associating inflammation and obesity is complex and encompass a diversity of factors; the inflammatory protein SAA may be one of them. In conclusion, our data describes the relationship between SAA, acute inflammation, sleep restriction and obesity.